The transformation of the camp theme in Sergei Lebedev’s novel “Oblivion” - Kalafatics, Zsuzsanna (Slavica, 2025)
Sergei Lebedev’s novel Oblivion offers an original reworking of the tradition of Russian camp prose. Its central themes are the legacy of Stalinist terror, the intergenerational transmission of trauma, and the necessity of a conscious resistance to their consequences. This paper explores how Lebedev, drawing on the concept of post-memory, intertwines personal family history with questions of collective memory, highlighting the destructive effects of silencing the past and the absence of accountability for historical crimes. At the core of this interpretation is an analysis of the narrator’s journey through space, time, and self-discovery, structured around the mythological motif of descent (katabasis). The funeral ritual plays a key role in the novel’s initiation structure: the symbolic burial and mourning of victims who vanished without a trace becomes an act of memory restoration, offering the possibility of reconciliation and a new beginning. Lebedev critically engages with contemporary Russian memory politics, stressing the moral imperative to uncover and give voice to the traumatic past.